DEVELOPMENT OF DIGITAL INNOVATION IN FINANCE - Herlina (Program Studi Perbankan Syariah, 2021)
Humans are always struggling with various needs and necessities of life, sometimes requiring them to interact with financial institutions, especially business people. Limited knowledge and access to bank has caused this community to become entangled in loan sharks. Contextual digital innovation to a new innovation is a solution that can change new services. Digital innovation is formed from technology made by a company to answer existing problems so as to create new products. Development of Digital Innovation in Islamic Bank Financing Communication and information technology developed rapidly in the Industrial Revolution 4.0 era which had a positive impact on the development of digital innovation in Islamic financial institutions. The purpose of this study is to determine the extent to which the development of digital innovation at Bank Rakyat Indonesia Syariah touches the wider community and meets financing targets as well as explores the negative impacts and handling of existing digital applications. This research method uses a qualitative approach with descriptive and semi-explorative levels of explanation, taking data through literature, mass media, social media and structured interviews as well as open discussions with informants. Data collection using non-participant observers. The results of the research are expected to be able to improve the digital application that is being used to attract financing at Bank Rakyat Indonesia Syariah which has merged into Bank Syariah Indonesia so that it can be more useful and safer in use, especially during this pandemic. Improvements in accelerating financing decisions that are more thorough, accurate and efficient by using standard and standard processes and approvals. The conclusion of this research is more directed to the improvement of application implementation and usage patterns in society.